Contrast echocardiographic assessment of the neonatal ductus arteriosus. Issue 5 (May 1986) - Knight, D B; Yu, V Y
Abstract : Contrast echocardiography is a safe and accurate method of diagnosing patent ductus arteriosus (PDA) in newborn infants. In this study the presence of PDA in very low birthweight infants receiving mechanical ventilation was investigated by contrast echocardiography. This was used as a basis for determining the accuracy of clinical signs and M mode echocardiography in the diagnosis of PDA. At the first contrast echocardiographic examination at a mean age of 49 hours PDA was found in 75% of infants. Clinical signs were inconsistent; 42% of the infants with PDA at the first examination had a murmur, no relation being found between PDA and heart rate or cardiothoracic ratio. Left atrial and left ventricular dimensions were significantly raised and left systolic time intervals significantly lower in the group with PDA. There was, however, considerable overlap, with the sensitivity of each measurement varying between 52% and 71%. Left systolic time interval combined with left ventricular:aortic root ratio gives the best differentiation between infants with or without PDA.